Análise da interação solo-estrutura em edifícios sobre estacas - ARAÚJO, Adrianne Carvalho de (2009)
The joined structure-foundation analysis of buildings is one of the studied themes of Soil- Structure Interaction (SSI). In this research, a numerical tool was developed using the Matlab program to evaluate the soil-structure interaction in buildings, where the problem has been studied in the last years, but has not became a current practice in civil engineering. The developed program, here named as AIEFE, predict the settlement using the Aoki and Lopes (1975) method, using as input data the reaction loads of building columns, calculated in any subroutine of spatial-portico analysis. The commercial program TQS was chosen as this subroutine in the present research. The found foundation settlements were converted in stiffness values and, then, inputted again in the structural analysis, predicting new settlements, but no more considering the foundations as fixed points . The method is iterative, aiming to reach the settlement (or load) convergence. Two examples of buildings supported by piled foundations were analyzed. The first one presented an almost square plant and the other one was typically rectangular. The SSI effects were analyzed in terms of column loads and also stiffness and foundations settlements during the constructive process of the 15-levels studied cases. During the construction of the first building levels, it was observed a greater load and settlement redistribution, due the lower structural stiffness. Using the foundation stiffness instead of settlement values was considered as an efficient process of convergence. It was also observed that the non-linear foundation behavior had a great influence in the structure load redistribution, even on advanced construction stages when the structure stiffness has a great value.